Analisis Yuridis Kepemilikan Rumah Susun oleh Warga Negara Asing Dalam Mewujudkan Kepastian Hukum - Sari, Retno Dewi Pulung; Udjan, Bernadeth Gisela Lema (Jurnal Spektrum Hukum PMIH UNTAG Semarang, 2023)
The issuance of Law Number 5 of 1960 concerning Basic Agrarian Regulations or what can be called UUPA is aimed at the welfare and prosperity of the Indonesian people. This policy is a form of protecting the rights of the Indonesian people which regulates ownership of flats. In its development, land in Indonesia has also followed developments with the existence of flats, namely residential places with vertical floors on a horizontal plot of land and consisting of units that can be owned and used by each owner individually as regulated in Law Number 20 of the Year 2011 concerning Flats. The regulations regarding flat ownership have been regulated in Law Number 6 of 2023 concerning Stipulation of Government Regulations instead of Law Number 2 of 2022 concerning Job Creation. However, there is legal uncertainty regarding these two laws and regulations so appropriate efforts are needed to realize legal certainty regarding ownership of flats by foreign citizens (WNA). The type of research that will be carried out is normative juridical research that uses a library study model. This research uses a statutory regulation approach. The literature study carried out by the author is on related literature which shows that there is legal uncertainty regarding the regulation of flat ownership by foreigners. Due to legal uncertainty, an ideal policy is needed to protect the rights of Indonesian citizens (WNI).